2017
DOI: 10.15376/biores.13.1.104-114
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Parameters of Different Modifications of Rape Straw (Brassica napus L.)

Abstract: Material alternatives to wood, such as rape straw, are needed for the production of composite materials. This study performed an analysis of rape straw as a composite material source for production. There were three types of rape straw particle modification: untreated particles as reference variant, boiling in water, and soaking in sodium hydroxide (NaOH) solution. The pH and calorific value were highest for the variant soaked in NaOH. The total elemental content and the elements on the rape straw surface vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Sample images with elemental distribution at the surface of scales are presented in Figure 2 . It was confirmed that carbon and oxygen have the highest percentage in lignocellulosic materials [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample images with elemental distribution at the surface of scales are presented in Figure 2 . It was confirmed that carbon and oxygen have the highest percentage in lignocellulosic materials [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the failure is not areal as in the previous cases, but rather spatial. The presence of residual Ca crystals (marked by arrows) in the structure of the exposed mesh also has a significant but unknown effect [9]. Overall, after evaluating the observations of all variants, the bonding quality after alkaline treatment using epoxy polyester adhesive is the best.…”
Section: Chemically Treated Particlesmentioning
confidence: 99%
“…Leaching in boiling water improves adhesion due to the partial removal of waxy substances from the particle surface [9]. The failure of the joint occurs at the adhesive and material interface (Figure 2a), but the cohesive failure in the material itself is also evident ( Figure 2b).…”
Section: Hydrothermally Treated Particlesmentioning
confidence: 99%
See 2 more Smart Citations